Analysis Of Economic Growth and Income Disparity Of Grdp Per Capita Regencies/Cities In South Sulawesi Province In 2016-2020 - Muhammad Hatta; Fatimah Fatimah; Nirmah Amir (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
This study aims to determine the classification of economic growth and the disparity in GRDP income per capita regencies/cities in South Sulawesi Province. The type of research used in research is the research of case studies with a quantitative descriptive approach. The data processed is secondary data obtained from the Central Statistics Agency of South Sulawesi Province in 2016–2020. The analytical methods used are the class typology for grouping economic growth and the Williamson Index for measuring development inequality. The results of this study show that the classification according to Klassen Typology which is included in the fast-growing and fast-growing areas is Pinrang Regency and Makassar City, the rapidly developing areas are Selayar Regency, Bantaeng Regency, Jeneponto Regency, Takalar Regency, Gowa Regency, Sinjai Regency, Barru Regency, Bone Regency, Soppeng Regency, Luwu Regency, Tana Toraja Regency, North Luwu Regency, North Toraja Regency and Palopo City, The developed but depressed areas are Maros County, Pangkajene and Islands Regency, Wajo County, East Luwu County, and Parepare City. Then, the relatively underdeveloped areas are Bulukumba Regency, Sidenreng Rappang Regency, and Enrekang Regency. The average level of inequality of the Williamson Index in the period in 2016-2020 in regencies/cities in South Sulawesi Province was 0.621.